Descomponiendo el efecto del gasto público en la tasa de cambio real: Una aproximación al caso Colombiano; Decomposing the effect of public spending on the real exchange rate: An approximation to the Colombian case - Julio Alonso; Luis Jaramillo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– This paper studies the relation between government spending composition and long-run behavior of Colombian real Exchange rate given the recomposition since 2004 from public consumption to public investment. Our results suggest that empirical models work better when the relative price of non-tradables is used as a measure of the real Exchange rate instead of an index based on the purchasing power parity. Besides, there is evidence that real exchange rate behavior is mainly explained by supply side factors and that without the recomposition, expected real Exchange rate would have been close to the observed one.
Keywords: F41; E62; C32; 330; government spending; real exchange rate; relative price of non-tradables; misalignment; Balassa-Samuelson